PENGARUH GOOD CORPORATE GOVERNANCE (GCG) DAN UKURAN BANK TERHADAP NON PERFORMING FINANCING (NPF) PADA PERBANKAN SYARIAH DI INDONESIA - Ayu LeviaTryana (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2019)
The purpose of this study is to analyze the effect of Good Corporate Governance and bank size on Non-Performing Financing. The population of this study is the Islamic Bank in Indonesia and the sampling was taken by using the purposive sampling method. Data analysis in this study used panel data regression using the e-views application. The results of this study indicate that the variable of good corporate governance is significant on Non Performing Financing (NPF) and the variable size of the bank is not significant on NonPerforming Financing (NPF).